Pornografi & pornoaksi : ditinjau dari hukum Islam - Djubaedah, Neng, 1948- (Jakarta : Prenada Media, 2004)
Pornography and sexual abuse according to Islamic law in Indonesia
Daftar pustaka : p. [355]-365
Keywords: Sex crimes (Islamic law); Pornography -- Law and legislation -- Indonesia; Pornography -- Religious aspects -- Islam -- Indonesia; Islamic law -- Indonesia